Personal Data Monetization in the Digital Economy - Yuyun P. Rahayu; Oktafiana Akmal; Yuni Shara (Nomico, 2026)
Personal data has become one of the most contested resources of the digital economy: it generates substantial economic value for platforms and intermediaries, while raising persistent questions about privacy, consent, and fairness. This article examines personal data monetization by combining an economic-opportunity perspective with a critical exploitation perspective, addressing a gap in the literature, which tends to treat these two views in isolation. Using a qualitative, literature-based method, twenty-five peer-reviewed and indexed sources published between 2021 and 2026 were analyzed through thematic-comparative synthesis, combining a reference collection assembled by the researcher with five additional sources located independently through recent, DOI-verified academic literature. The novelty of this study lies in its dual-lens analytical framework, which positions data monetization simultaneously as a legitimate economic asset and as a site of structural power asymmetry between platforms and data subjects, and in its comparative reading of global practice against Indonesia's Personal Data Protection Law. Findings show that monetization models range from targeted advertising and data brokerage to consent-based data marketplaces and privacy-preserving technical architectures, each carrying distinct opportunity and risk profiles. Regulatory frameworks such as the GDPR and Indonesia's PDP Law reduce, but do not eliminate, exploitative practices, particularly where consent remains structurally asymmetric. The article concludes that sustainable data monetization requires embedding fairness, transparency, and data-subject agency into market design itself, rather than treating compliance as a sufficient safeguard.